0021 Using Simulation To Enhance General Practice Training: A 'crash Course' In Acute Paediatrics. (1st November 2014) - Chase, Clarissa; Edelman, James; Lynch, Jackie; Sykes, Kim; Pryde, Kate; Baird, Jim
Abstract : Background: Children comprise 40% of a typical GP's workload, however only 55% of GP trainees will undertake a hospital-based paediatric placement during their training. 1 GP trainees acknowledge that they are often nervous about managing acute paediatric illness in primary care, 2 and recent publications from The Royal Colleges of General Practitioners and Paediatrics and Child Health have recommended that GP training should include more focus on paediatrics. 3, 4 Methodology: We designed a one-day course that uses multiple simulations to allow GP trainees to experience the presentation, diagnosis and management of acute paediatric illness in primary care. Trainees are required to provide emergency assessment and treatment in real-time using low and high fidelity manikins, with actors as simulated parents. The course is facilitated by paediatric registrars and nurses to allow discussion and learning in a non-hierarchical environment. Written summaries are provided for each simulation to consolidate key learning points and direct to further resources. Results/outcomes: A pre- and post-course questionnaire will be completed by each candidate, focusing on their confidence in the management of the simulated presentations. Follow-up questionnaires (after 6 months) will assess candidates' retention of information and the impact of simulation training in their daily practice. A pilot course will run in August 2014 with a volunteer group of GP trainees (n = 20). Potential impact: We believe an intensive simulation course provides GP trainees the opportunity to manage paediatric emergencies in a safe, facilitated environment, before using these skills in real life. We intend this to highlight trainees' learning needs and improve confidence prior to independent practice. We plan to expand this course to include all GP trainees in our region before the end of their training, and to offer it to existing GPs as a refresher in acute paediatrics. References: Walker V. Paediatric training for GP VTS trainees: are we meeting the requirement? Educ Prim Care 2009;20(1):28–33(6) Burkes M. Tips for GP trainees working in paediatrics. Br J Gen Pract 2011;61(582):68–9 Clements K. Opening the door to better healthcare: Ensuring general practice is working for children and young people. The National Children's Bureau. 2013 Royal College of Paediatrics and Child Health (RCPCH). Back to Facing the Future: An Audit of Acute Paediatric Service Standards in the UK. 2013